Implementation of Targhib And Tarhib Methods to Teach Aqidah and Akhlaq Subject in Madrasah - Nurhamzah Nurhamzah; Risal Qori Amarullah (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2021)
This study is aimed at investigating targib and tarhib method in terms of planning, implementation, supporting and inhibiting factors for the implementation, evaluation and success rate of application. This research applied qualitative method using descriptive analytic. The data were collected using observation, interviews, and documentation. Data were analysed by selecting, sorting data obtained, analysing and drawing conclusions. The findings show that the planning was designed in terms of learning strategies, techniques and tactics in the document of lesson plan. The implementation was in accordance with the planning written in the learning steps in the document of lesson plan. The supporting factors included innovative and competent teachers in their fields, full support from the principal, support from the teacher council and school staff, and the availability of facilities and infrastructure. The inhibiting factors covered the differences in the students’ background and the location of the classrooms which is next to public roads and residents' houses. The evaluation was done by observing students’ attitudes and administering the oral tests in learning. The success rate of implementation can be seen from the increase in the students’ awareness to behave akhlak karimah in everyday life.